Influence of CYP3A5 Genetic Polymorphism on Long-Term Renal Function in Chinese Kidney Transplant Recipients Using Limited Sampling Strategy and Abbreviated Area Under the Curve for Tacrolimus Monitoring. (September 2020) - Cheung, Chi Yuen; Chan, Koon Ming; Wong, Yuen Ting; Chak, Wai Leung; Bekers, Otto; van Hooff, Johannes P.
Introduction: Although the association between CYP3A5 gene polymorphism and tacrolimus dosing requirements was well established, the impact on how CYP3A5 genotype affects the acute rejection and long-term renal function in patients who received kidney transplants and were treated with tacrolimus remained controversial. Design: Sixty-seven Chinese patients with kidney transplants receiving de novo tacrolimus-based immunosuppressive therapy with known CYP3A5 genotype were divided into 2 groups. Those with at least 1 CYP3A5*1 allele were CYP3A5 expressers while homozygotes for the mutant allele CYP3A5*3 were nonexpressers. Instead of trough level, our center used abbreviated area under the curve for tacrolimus monitoring. Primary outcome was the long-term renal function between both groups while secondary outcomes included the weight-adjusted daily tacrolimus dose, graft survival, incidence of biopsy-proven acute rejection (BPAR), opportunistic infection, and cancer. Results: Thirty-five (52.2%) patients were CYP3A5 expressers while 32 were nonexpressers. Mean daily tacrolimus dose in the CYP3A5 expressers and nonexpressers was 0.08 (0.03) and 0.05 (0.02) mg/kg, respectively ( P < .01). Starting from 1-month posttransplant, the renal function was comparable between both groups, which persisted up to 10-year. Ten patients experienced BPAR rejection and there was no significant difference in the rejection-free survival between both groups ( P = .87). There was also no significant difference in the death-censored graft survival between both groups ( P = .86). Finally, the incidence of opportunistic infection and posttransplant cancer was similar between them. Discussion: There was no significant difference in renal function, graft survival, and acute rejection between CYP3A5 expressers and nonexpressers.